Evaluation Of Relationship Causes Of The Return Process In The Supply Chain Of The Textile Industry - Yuliawati, Evi -; Putri, Vitara Injang Ridhani Ferninda; Brilliana, Clora Widya (Politeknik APP Jakarta, 2022)
This research focuses on the return process, the process where consumers decide to return the product after receiving an order or after making a purchase. This incident is not desired by the company, because it has the potential to reduce profits and consumer loyalty. However, the company is aware that the return process cannot be avoided. So this research aims to evaluate the factors that have the potential to cause the return process by using the Interpretive Structural Modeling (ISM) Methodology. This research case study was conducted on a textile company that serves orders for school uniforms, office uniforms, moslem clothes, etc. Nine factors were identified, that are: off-season, overstock, delivery error, incorrect size, incorrect color, quality issue, change mind, damaged item, and incorrect product, which are the reasons consumers carry out the return process. The results of the ISM-based model and MICMAC analysis mapping show that the quality issue factor is the key reason for consumers to make the return process. The strategy of handling presses return in connection with these factors is carried out by developing a system that supports customer support work to maintain consumer loyalty. Through the ISM methodology, companies can simplify complex problems, so they focus on the factors that are the root of the problem to be able to design strategies to deal with them.